PENGARUH SOFT SKILL DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN HOTEL PELANGI MALANG - Euis Emiliasari; Agus Widarko; Afi Rachmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
Abstract This study aims 1) To determine the effect of soft skill and work motivation simultaneously on employee performance, 2) To know the effect of variable soft skill and work motivation partially to employee performance. The population in this study is the total employee Hotel Pelangi Malang, amounting to 80 employees. The analysis used is multiple linear regression analysis. Based on statistical test F showed that both variables have an effect because it has a significance value less than 5% real level. Result of t test show significant influence from both variable to employee performance Pelangi Hotel Malang, both have t value> of t table. R square results obtained results of 0.701 means there is a strong relationship between soft skills and work motivation on employee performance Pelangi Hotel Malang. R square of 0.701 which means that soft skill and work motivation in explaining the fluctuation of employee performance variable is 70,1%, while the rest of 29,9% influenced by other factors besides soft skill and work motivation Keywords: Soft Skill, Work Motivation, Employee Performance